The mining sector taxation and the environment recovery in Peru, 2011-2016 - Valencia Gutiérrez, Adolfo (2020)
Objective: Determine if the taxes amount formal companies in the Peruvian mining sector compensates the environment damage or ecosystems caused by their activities. Method: Research of deductive, non-experimental and transversal quantitative approach, explanatory – causal level. The target population consisted of 49 formal mining companies that generate taxes on the Peruvian State in 15 regions, evidenced with normative documents from the Ministry of the Environment. Results: The mining sector tax revenues for the conservation and restoration of the destroyed environment by mining; likewise, the Ministry of the environment management has been inefficient so it develops the need for an environmental taxation. Conclusions: It corroborated that the taxation of the mining sector has been part of the Peruvian state income; however, it could not be determined whether or not it compensates to the environment damage, since the state has not elaborated, formulated or implemented any project in relation to the conservation and restoration of the environment.